The use of the ph1b mutant to induce recombination between the chromosomes of wheat and barley - Rey, María-Dolores; Calderón, María C.; Prieto, Pilar (Frontiers in Plant Science, 2015)
Intensive breeding has led to a narrowing in the genetic base of our major crops. In wheat, access to the extensive gene pool residing in its many and varied relatives (some cultivated, others wild) is hampered by the block on recombination imposed by the Ph1 (Pairing homoeologous 1) gene. Here, the ph1b mutant has been exploited to induced allosyndesis between wheat chromosomes and those of both Hordeum vulgare (cultivated barley) and H. chilense (a wild barley). A number of single chromosome Hordeum sp. substitution and addition lines in wheat were crossed and backcrossed to the ph1b mutant to produce plants in which pairing between the wheat and the non-wheat chromosomes was not suppressed by the presence of Ph1. Genomic in situ hybridization was applied to almost 500 BC1F2 progeny as a screen for allosyndetic recombinants. Chromosome rearrangements were detected affecting H. chilense chromosomes 4Hch, 5Hch, 6Hch and 7Hch and H. vulgare chromosomes 4Hv, 6Hv and 7Hv. Two of these were clearly the product of a recombination event involving chromosome 4Hch and a wheat chromosome.